Drought reduces tree growing season length but increases nitrogen resorption efficiency in a Mediterranean ecosystem - R. Lobo-do-Vale; C. Kurz Besson; M. C. Caldeira; M. M. Chaves; J. S. Pereira (Biogeosciences, 2019)
Mediterranean ecosystems are hotspots for climate change, as the highest impacts are forecasted for the Mediterranean region, mainly by more frequent and intense severe droughts. Plant phenology is a good indicator of species' responses to climate change. In this study, we compared the spring phenology of cork oak trees (Quercus suber), an evergreen species, over 2 contrasting years, a mild year (2004) and a dry year (2005), which was the most severe drought since records exist. We evaluated the timing of occurrence, duration, and intensity of bud development, budburst, shoot elongation, trunk growth, and leaf senescence (phenophases) and assessed the nitrogen resorption efficiency from senescent to green leaves. The temperature was the main driver of budburst. Nevertheless, water had the main role of constraining all the other phenophases by strongly reducing the growing season length (−48 %) and consequently the tree growth. Basal area increment was the most affected growth variable (−36 %), although it occurred at a similar rate in the 2 years. Shoot elongation was also reduced (−21 %), yet elongation occurred at a higher rate in the dry year compared to the mild year. Leaf senescence during the bulk period was higher in the dry year, in which leaves were shed at the same rate over a longer period. Nitrogen concentrations in green and senescent leaves were affected by drought and nitrogen resorption efficiency increased remarkably (+22 %). Our results highlight the importance of studying different phenological metrics to improve our understanding of the ecosystem's responses to climate change. The faster dynamics observed in shoot elongation, while all other phenophases developed at the same rate, indicate that leaf area development is privileged in cork oak. Water availability was the main driver of spring growth in this Mediterranean ecosystem; however, growth may be affected by complex interplays between precipitation and temperature, such as higher temperatures during dry winters or heatwaves during spring, that are likely to result in water stress. Longer studies are needed to disentangle those interplays. Finally, a higher nitrogen resorption efficiency in response to drought appears to be an adaptive trait that mitigates the limitation in nitrogen uptake by the roots during drought and contributes to improving tree fitness in the short term but will probably exert a negative feedback on the nitrogen cycle in the long term, which might affect the ecosystem functioning under the forecasted droughts.